PHYLOGENY OF SOME MIDDLE AMERICAN PITVIPERS BASED ON A CLADISTIC ANALYSIS OF MITOCHONDRIAL 12S AND 16S DNA SEQUENCE INFORMATION - Werman, Steven D.; Crother, Brian I.; White, Mary E. (Contemporary Herpetology, 1999)
The cladistic relationships of several Middle American pitvipers representing the genera Bothrops (sensu stricto), Bothriechis, Cerrophidion, Lachesis and Porthidium were determined using mitochondrial 12S and 16S DNA sequence information. Maximum parsimony analyses were performed using PAUP on aligned sequences that included published information for related taxa. Two sets of analyses were conducted: one disregarding gaps in the aligned matrix, and another with gaps treated as a fifth base. When gaps were excluded resolution declined, although the general arrangement of the taxa changed little. A consistent relationship was the grouping of ((Porthidium, Bothriechis) Lachesis). The placement of Lachesis, as nested within other bothropoid genera, is only partially supported by results of other authors. The arrangement of Crotalus, Bothrops and Cerrophidion was ambiguous when gaps were discounted. In both trees, Agkistrodon was basal to the New World forms. The remaining genera, Trimeresurus (Protobothrops), Vipera, Azemiops, and Coluber, were uniformly distant to the former taxa. Also of interest is the lack of close relationship, based on the DNA data here and elsewhere, between Bothrops and Porthidium. This is in striking contrast to results based on morphologic and allozymic analyses of previous studies. It is concluded that additional DNA sequence information from a larger sample of taxa will be necessary to better assess the phylogenetic relationships among Middle American and related pitvipers.